Det id(EU)logiska samtalet En skiljelinje och två av dess ideologiska dimensioner observerade hos svenska partier i samband med folkomröstningen om EMU - Karlsson,Anneli (2010)
This study examines an ideological content related to Swedish political parties in regards to EMU. In order to do so theoretical starting points has been used, originating from the concepts of cleavages and dimensions. More specifically, the relevant cleavage in this study is the one called: nationalism-supranationalism, and the study also includes two of its dimensions concerning different social models and their main means. The method used in the study is ideology analysis which is carried out by the use of constructed parameters derived from the theoretical starting points. The study shows differences between the Swedish political parties when it came to their ideological focus. The parties negative against the EMU were generally more ideological, and more concerned with the purposes of the project, while the parties positive towards the EMU were less ideological, and more concerned with the political means.
Keywords: partier; ideologi; skiljelinjer; dimensioner; partitidningar; EMU